Dinactin: A New Antitumor Antibiotic with Cell Cycle Progression and Cancer Stemness Inhibiting Activities in Lung Cancer - Anchalee Rawangkan; Pattama Wongsirisin; Grissana Pook-In; Achiraya Siriphap; Atchariya Yosboonruang; Anong Kiddee; Jureeporn Chuerduangphui; Nanthawan Reukngam; Acharaporn Duangjai; Surasak Saokaew; Ratsada Praphasawat (MDPI AG, 2022)
Lung cancer, especially non-small cell lung cancer (NSCLC), is one of the most complex diseases, despite the existence of effective treatments such as chemotherapy and immunotherapy. Since cancer stem cells (CSCs) are responsible for chemo- and radio-resistance, metastasis, and cancer recurrence, finding new therapeutic targets for CSCs is critical. Dinactin is a natural secondary metabolite produced by microorganisms. Recently, dinactin has been revealed as a promising antitumor antibiotic via various mechanisms. However, the evidence relating to cell cycle progression regulation is constrained, and effects on cancer stemness have not been elucidated. Therefore, the aim of this study is to evaluate the new function of dinactin in anti-NSCLC proliferation, focusing on cell cycle progression and cancer stemness properties in Lu99 and A549 cells. Flow cytometry and immunoblotting analyses revealed that 0.1-1 µM of dinactin suppresses cell growth through induction of the G0/G1 phase associated with down-regulation of cyclins A, B, and D3, and cdk2 protein expression. The tumor-sphere forming capacity was used to assess the effect of dinactin on the cancer stemness potential in NSCLC cells. At a concentration of 1 nM, dinactin reduced both the number and size of the tumor-spheres. The quantitative RT-PCR analyses indicated that dinactin suppressed sphere formation by significantly reducing expression of CSC markers (i.e., ALDH1A1, Nanog, Oct4, and Sox2) in Lu99 cells. Consequently, dinactin could be a promising strategy for NSCLC therapy targeting CSCs.